A Pilocytic Astrocytoma Mimicking a Clinoidal Meningioma. (13th March 2014) - Hong, Christopher S.; Lehman, Norman L.; Sauvageau, Eric
Abstract : Pilocytic astrocytomas and meningiomas are benign, primary brain tumors that may involve the optic tract. Classically, the presence of a dural "tail" sign may differentiate a meningioma from other intracranial lesions. In this report, we describe a mass with the typical appearance of a clinoidal meningioma on magnetic resonance imaging (MRI) but postoperatively diagnosed as a pilocytic astrocytoma. This case illustrates the rare occurrence of a pilocytic astrocytoma mimicking a meningioma on MRI.